Is the Implementation of the Taxation Omnibus Law Important for Dividend Policy? - Haryadi, Dedi; Leon, Hengky; Louw, Febriana; Indawati Halim, Kusuma; Novianty, Novianty (International Journal of Economics and Financial Issues, 2025)
This study investigates the impact of the implementation of Indonesia’s Taxation Omnibus Law on corporate dividend policy, with a particular focus on the moderating role of institutional ownership. Utilizing panel data regression with a Random Effects Model approach, the analysis is conducted on 37 companies listed in the LQ-45 index over the period 2017–2024. The empirical findings reveal that the tax reform positively influences dividend yield, yet has no significant effect on dividend per share (DPS). Moreover, the interaction between institutional ownership and tax reform weakens the impact of the reform on DPS. Theoretically, these results highlight that the effectiveness of tax policy reforms is contingent upon a firm’s ownership structure. From a policy perspective, the findings underscore the need for targeted tax incentives that align with corporate governance characteristics to effectively influence dividend distribution decisions. The novelty of this research lies in its focus on the Taxation Omnibus Law and its implications for dividend payout behavior, while incorporating institutional ownership as a moderating variable—an area that has received limited attention in prior studies on tax reform and corporate financial policy.